Medium- and Long-Term Energy Demand of China and Energy Transition Pathway Toward Carbon Neutrality - Huang Zhen; Xie Xiaomin; Zhang Tingting (中国工程科学, 2022)
China is the world’s largest energy consumer and carbon emitter. Its coal-dominated energy structure and heavy industries bring considerable challenges for achieving the carbon peaking and carbon neutrality goals and for realizing high-quality energy development; this necessitates research on energy transition pathways. Herein, the study reviews the current status of China's energy development and predicts the medium- and long-term energy demand and energy transition trends in the country. Our results indicate that the total primary energy demand of China will reach 5.56 × 109 to 5.96 × 109 tons of standard coal in 2035. The CO2 emission intensity per unit of GDP in 2035 will decrease by 77.6% ‒ 81.5% compared with that in 2005. Energy-related CO2 emissions will peak during the 15th Five-Year Plan period. Improving energy efficiency, expanding renewable energy application, promoting the carbon capture, storage and utilization technology, and developing hydrogen energy and renewable synthetic fuels are the major technical measures for reducing energy-related CO2 emissions. Moreover, technological innovation is the core driving force for promoting the green and low-carbon transformation of key areas in China. Furthermore, suggestions are proposed from the aspects of energy conservation,renewable energy development, technological innovation,  and coordination of the legal system, technologies, and the market.